2001
DOI: 10.1073/pnas.221198698
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of ergovaline from a grass– Neotyphodium endophyte symbiosis by genetic modification of the endophyte

Abstract: The fungal endophytes Neotyphodium lolii and Neotyphodium sp. Lp1 from perennial ryegrass (Lolium perenne), and related endophytes in other grasses, produce the ergopeptine toxin ergovaline, among other alkaloids, while also increasing plant fitness and resistance to biotic and abiotic stress. In the related fungus, Claviceps purpurea, the biosynthesis of ergopeptines requires the activities of two peptide synthetases, LPS1 and LPS2. A peptide synthetase gene hypothesized to be important for ergopeptine biosyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
193
0
2

Year Published

2005
2005
2006
2006

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 170 publications
(201 citation statements)
references
References 41 publications
6
193
0
2
Order By: Relevance
“…This experiment showed that the level of b-tubulin transcript in planta was ;1/ 80th the level in mycelia ( Figure 6A), a result consistent with estimates of endophyte biomass in perennial ryegrass of between 0.4 and 1.9% (Panaccione et al, 2001;Young et al, 2005). Semiquantitative RT-PCR expression analysis showed that noxA is weakly expressed in axenic culture but strongly expressed in planta ( Figure 6A).…”
Section: E Festucae Noxa Is Preferentially Expressed In Plantasupporting
confidence: 81%
See 1 more Smart Citation
“…This experiment showed that the level of b-tubulin transcript in planta was ;1/ 80th the level in mycelia ( Figure 6A), a result consistent with estimates of endophyte biomass in perennial ryegrass of between 0.4 and 1.9% (Panaccione et al, 2001;Young et al, 2005). Semiquantitative RT-PCR expression analysis showed that noxA is weakly expressed in axenic culture but strongly expressed in planta ( Figure 6A).…”
Section: E Festucae Noxa Is Preferentially Expressed In Plantasupporting
confidence: 81%
“…Protection of the symbiotum from insect and small animal herbivory through endophyte synthesis of bioprotective secondary metabolites (alkaloids) is the best-studied benefit of this association (Bush et al, 1997;Lane et al, 2000). Genes for the biosynthesis of the four main classes of bioprotective alkaloids have now been cloned, including genes for the biosynthesis of ergot alkaloids (Panaccione et al, 2001;Wang et al, 2004), lolines (Spiering et al, 2002(Spiering et al, , 2005, peramine (Tanaka et al, 2005), and indole-diterpenes (Young et al, 2005). Expression studies have shown that the genes for all four pathways are preferentially and highly expressed in planta (Spiering et al, 2002;Tanaka et al, 2005;Young et al, 2005), suggesting that host-specific signaling is required for the induction of these pathways.…”
Section: Introductionmentioning
confidence: 99%
“…All A. fumigatus sequences described in this paper are located on assembly 92 (chromosome 2, formerly assembly 72) between nucleotides 2894958 and 2926335. The presence of sequences in the A. fumigatus genome that are similar to known or putative ergot alkaloid biosynthesis genes was assessed by application of the tblastn algorithm (1) at the National Center for Biotechnology Information website (www.ncbi.nlm .nih.gov) with the deduced protein sequences of DMAT synthase of Claviceps fusiformis (24) and LPS1 of Neotyphodium lolii (16) or C. purpurea (26) as query sequences. The nature of genes linked to the ergot alkaloid biosynthesis genes or candidate genes was investigated by retrieving contiguous 2-kb segments of DNA from the A. fumigatus genome and querying the nonredundant protein database of the National Center for Biotechnology Information with these sequences by application of the blastx search algorithm (1).…”
Section: Methodsmentioning
confidence: 99%
“…A gene encoding lysergyl peptide synthetase 1 (LPS1), one of two components of the lysergyl peptide synthetase complex responsible for assembly of ergopeptines from lysergic acid and three amino acids (20,28), was also knocked out in Neotyphodium sp. strain Lp1 (16). LPS1-deficient knockout mutants failed to produce ergopeptines and simple amides of lysergic acid but still produced clavine ergot alkaloids (15,16).…”
mentioning
confidence: 99%
See 1 more Smart Citation